A Vibrio cholerae anti-phage system depletes nicotinamide adenine dinucleotide to restrict virulent bacteriophages - Yishak A. Woldetsadik; David W. Lazinski; Andrew Camilli (mBio)
ABSTRACT Bacteria and their predatory viruses (bacteriophages or phages) are in a perpetual molecular arms race. This has led to the evolution of numerous phage defensive systems in bacteria that are still being discovered, as well as numerous ways of interference or circumvention on the part of phages. Here, we identify a unique molecular battle between the classical biotype of Vibrio cholerae and virulent phages ICP1, ICP2, and ICP3. We show that classical biotype strains resist almost all isolates of these phages due to a 25-kb genomic island harboring several putative anti-phage systems. We observed that one of these systems, Nezha, encoding SIR2-like and helicase proteins, inhibited the replication of all three phages. Bacterial SIR2-like enzymes degrade the essential metabolic coenzyme nicotinamide adenine dinucleotide (NAD+), thereby preventing replication of the invading phage. In support of this mechanism, we identified one phage isolate, ICP1_2001, which circumvents Nezha by encoding two putative NAD+ regeneration enzymes. By restoring the NAD+ pool, we hypothesize that this system antagonizes Nezha without directly interacting with its proteins and should be able to antagonize other anti-phage systems that deplete NAD+.IMPORTANCEBacteria and phages are in a perpetual molecular arms race, with bacteria evolving an extensive arsenal of anti-phage systems and phages evolving mechanisms to overcome these systems. This study identifies a previously uncharacterized facet of the arms race between Vibrio cholerae and its phages. We identify an NAD+-depleting anti-phage defensive system called Nezha, potent against three virulent phages. Remarkably, one phage encodes proteins that regenerate NAD+ to counter the effects of Nezha. Without Nezha, the NAD+ regeneration genes are detrimental to the phage. Our study provides new insight into the co-evolutionary dynamics between bacteria and phages and informs the microbial ecology and phage therapy fields.